2009
DOI: 10.1128/aem.01796-08
|View full text |Cite
|
Sign up to set email alerts
|

Stress- and Growth Rate-Related Differences between Plate Count and Real-Time PCR Data during Growth of Listeria monocytogenes

Abstract: To assess the overestimation of bacterial cell counts in real-time PCR in relation to stress and growth phase, four different strains of L. monocytogenes were exposed to combinations of osmotic stress (0.5 to 8% [vol/vol] NaCl) and acid stress (pH 5 to 7) in a culture model at a growth temperature of 10°C or were grown under optimal conditions. Growth curves obtained from real-time PCR, optical density, and viable count data were compared. As expected, optical density data revealed entirely different growth cu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
18
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 34 publications
(37 reference statements)
3
18
1
Order By: Relevance
“…Findings by others support the existence of discrepancies between culture-dependent and culture-independent measurements, with concentrations determined by culture-dependent methods being smaller in each case (12,32). In our study, the greatest differences were always observed during the lag phase, and these discrepancies decreased as the cultures entered exponential phase.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Findings by others support the existence of discrepancies between culture-dependent and culture-independent measurements, with concentrations determined by culture-dependent methods being smaller in each case (12,32). In our study, the greatest differences were always observed during the lag phase, and these discrepancies decreased as the cultures entered exponential phase.…”
Section: Discussionsupporting
confidence: 64%
“…Bacterial concentrations determined by qPCR are comparable to those measured by culturing during the exponential phase of growth (32). However, under less optimal conditions, such as during the stationary phase of growth, when nutrients are depleted and metabolites accumulate (22), culturable concentrations decrease, while qPCR-based concentrations remain unchanged (32).…”
mentioning
confidence: 60%
See 1 more Smart Citation
“…The traditional predictive model was based on microbial growth data obtained by culture-dependent methods, where the process was rather time-consuming and labor-intensive (Ye et al 2013;Wang et al 2014). Recently, a few studies have reported that molecular methods could be used for construction of predictive models to describe the behavior of bacteria in food (Reichert-Schwillinsky et al 2009;Ye et al 2013Ye et al , 2014Liao et al 2015). As a novel molecular method, this PMA TaqMan-based multiplex real-time PCR method applied to construct predictive models had some remarkable advantages.…”
Section: Discussionmentioning
confidence: 99%
“…1-2 m in length [10,11], and it is recognized worldwide as one of the most important food-borne pathogens of great concern for the food industries. This bacterium has the peculiarity that it can survive or even grow at low temperatures [12,13].…”
Section: Introductionmentioning
confidence: 99%